Prevalence of dementia among older age people and variation across different sociodemographic characteristics: a cross-sectional study in BangladeshResearch in context - Aliya Naheed; Maliha Hakim; Md Saimul Islam; Md Badrul Islam; Eugene Y.H. Tang; Abdul Alim Prodhan; Mohammad Robed Amin; Blossom C.M. Stephan; Quazi Deen Mohammad (Elsevier, 2023)
Summary: Background: Dementia is a significant global health issue, particularly for low-income and middle-income countries which majorly contribute to the dementia cases reported globally (67%). We estimated the prevalence of dementia among older people in Bangladesh and compared the estimate across different sociodemographic characteristics and divisions. Methods: A cross-sectional study was conducted in 2019 among individuals aged 60 years or older in seven administrative divisions in Bangladesh. Equal numbers of male and female participants were recruited from each division through a multi-stage random sampling technique. Recruitment was proportionally distributed in urban and rural areas in each division. Following consent, the Mini Mental State Examination (MMSE) was performed on all participants. Dementia was defined as an MMSE score of <24 out of 30. Data on age, sex, education, marital status, occupation, socioeconomic status, and type of community (urban or rural) were obtained using a structured questionnaire to compare the prevalence of dementia across different sociodemographic characteristics. Findings: Between January and December 2019, 2795 individuals were recruited including ∼400 from each of the seven administrative divisions. The mean age was 67 years (SD: 7), 68% were from rural areas and 51% were female. The prevalence of dementia was 8.0% (95% CI: 7.0-8.9%) with variations across age, sex, education, marital status, occupation, and division. No variations in prevalence were observed across urban/rural locations or socioeconomic status. After adjusting for age, sex, education, occupation and marital status, the odds of dementia was two times higher in females than males (OR: 2.15, 95% CI: 1.43-3.28); nine times higher in people aged ≥90 years than people aged 60-69 years (OR: 9.62, 95% CI: 4.79-19.13), and three times higher in people with no education compared to those who had completed primary school (OR: 3.10, 95% CI: 1.95-5.17). Interpretations: The prevalence of dementia is high in Bangladesh and varies across sociodemographic characteristics with a higher prevalence among females, older people, and people with no education. There is an urgent need to identify the key risk factors for dementia in developing countries, such as Bangladesh, to inform the development of context-relevant risk reduction and prevention strategies. Funding: None.